SnO2/ZnO Heterostructure as an Electron Transport Layer for Perovskite Solar Cells - Albuquerque, Diego Aparecido Carvalho [UNESP]; Ramos, Raul [UNESP]; Ireno, Caio Eduardo Do Prado; Martins, Everson [UNESP]; Durrant, Steven F. [UNESP]; Bortoletoa, José Roberto Ribeiro [UNESP] (FapUNIFESP (SciELO), 2021)
This work reports a study of the room-temperature synthesis of a SnO2/ZnO bilayer by magnetron sputtering. Morphological, optical, and electrical properties of the bilayer were investigated for different thicknesses of SnO2. Morphology was studied using profilometry and field emission scanning electron microscopy. The optical transmittances of the ZnO films and of the SnO2/ZnO combination were high (about 80%) in the visible, and the SnO2 film did not alter the optical properties of the ZnO, which would act as a transparent contact electrode in a perovskite solar cell.
Keywords: Doped tin oxide; Etl; Psc; Solar energy